A silicon nitride waveguide-integrated chemical vapor deposited graphene photodetector with 38 GHz bandwidth. Issue 46 (15th November 2018) - Gao, Yun; Tsang, Hon Ki; Shu, Chester
Abstract : We demonstrate a high-speed chemical vapor deposited graphene-on-silicon nitride waveguide photodetector. Abstract : We demonstrate a high-speed chemical vapor deposited graphene-on-silicon nitride waveguide photodetector. The device is designed with grating-like metal contact to reduce the channel spacing. Benefiting from the narrow channel spacing, a calculated transit-time-limited bandwidth of 111 GHz is derived. The resistance–capacitance-limited bandwidth is also improved due to the small relative permittivity of silicon nitride. At a wavelength of 1550 nm, we measured an electro-optic bandwidth of 38 GHz under zero bias and an intrinsic responsivity of 13 mA W −1 at 0.1 V reverse bias with a 6 μm detection length.